ACCOUNTING FOR THE QUALITY OF MANAGEMENT IN THE ASSESSMENT OF BUSINESS VALUE - V. I. Busov (Вестник университета)
The expediency of expanding the scope of application has been justified and methods of using the quality parameter of the company’s management in determining its value using the methods of revenue and comparative approaches have been proposed. In calculating the discount rate, instead of the expert assessment method used in practice, a method for calculating the management risk premium to the risk-free rate, which gives a more objective result, has been offered. The quality of management has been considered as one of the main factors of non-systematic risks, expressed in the socio-economic efficiency of the company, in the calculations of which it has been proposed to apply a resource-target approach. In a comparative approach to evaluating the value of a company, the quality of management has been used as one of the criteria for selecting similar companies.